Applying generalized allometric regressions to predict live body mass of tropical and temperate arthropods. Issue 24 (6th December 2018) - Sohlström, Esra H.; Marian, Lucas; Barnes, Andrew D.; Haneda, Noor F.; Scheu, Stefan; Rall, Björn C.; Brose, Ulrich; Jochum, Malte
Abstract: The ecological implications of body size extend from the biology of individual organisms to ecosystem‐level processes. Measuring body mass for high numbers of invertebrates can be logistically challenging, making length–mass regressions useful for predicting body mass with minimal effort. However, standardized sets of scaling relationships covering a large range in body length, taxonomic groups, and multiple geographical regions are scarce. We collected 6, 212 arthropods from 19 higher‐level taxa in both temperate and tropical locations to compile a comprehensive set of linear models relating live body mass to a range of predictor variables. We measured live weight (hereafter, body mass), body length and width of each individual and conducted linear regressions to predict body mass using body length, body width, taxonomic group, and geographic region. Additionally, we quantified prediction discrepancy when using parameters from arthropods of a different geographic region. Incorporating body width into taxon‐ and region‐specific length–mass regressions yielded the highest prediction accuracy for body mass. Using regression parameters from a different geographic region increased prediction discrepancy, causing over‐ or underestimation of body mass depending on geographical origin and whether body width was included. We present a comprehensive range of parameters for predicting arthropod body mass and provide guidance for selecting optimal scaling relationships. Given the importance of body mass for functional invertebrate ecology and the paucity of adequate regressions to predict arthropod body mass from different geographical regions, our study provides a long‐needed resource for quantifying live body mass in invertebrate ecology research. Abstract : The ecological implications of body size extend from the biology of individual organisms to ecosystem‐level processes. Length–mass regressions are a powerful tool to predict body mass based on morphological traits of organisms. We present a comprehensive range of parameters for predicting arthropod body mass based on body length, width, taxonomy, and geographic origin.